Optimizing Lidocaine Dosing in Hepatectomy Patients: A Population Pharmacokinetic Study of Active Metabolites - He C; Qi X; Liu Y; Jin Y; Zhang M; Zhang Y; Fu L; Zheng L; Tu F; Wang Z (Drug Design, Development and Therapy)
Chaoqun He,1– 3 Xiaohui Qi,1,3 Yixian Liu,1,3 Ying Jin,1,3 Mengyu Zhang,1,3 Yang Zhang,4 Lisha Fu,1,3 Li Zheng,1,3 Faping Tu,2 Zhenlei Wang1,3 1Department of Pharmacy, NMPA Key Laboratory for Clinical Research and Evaluation of Innovative Drug, West China Hospital, Sichuan University, Chengdu, Sichuan, 610041, People’s Republic of China; 2Department of Anesthesiology, Affiliated Hospital of North Sichuan Medical College, Nanchong, Sichuan, 637000, People’s Republic of China; 3Clinical Trial Center, West China Hospital, Sichuan University, Chengdu, Sichuan, 610041, People’s Republic of China; 4Department of Anesthesiology, Suining Central Hospital, Suining, Sichuan, 629000, People’s Republic of ChinaCorrespondence: Faping Tu, Email tfpnc@163.com Zhenlei Wang, Email wangzhenlei@wchscu.cnBackground: Lidocaine and its active metabolites are metabolized mainly by the liver, and liver-compromised may slow the metabolism of lidocaine and its active metabolites. In addition to excessive lidocaine, accumulated active metabolites may also lead to lidocaine-related toxicity in liver-compromised patients. This study aimed to describe the population pharmacokinetics of lidocaine and its active metabolites in partial hepatectomy patients and propose a novel drug regimen involving lidocaine-weighted active metabolites.Methods: The concentrations of lidocaine and its active metabolites from thirty-five patients underwent partial hepatectomy were analysed by non-linear mixed-effects models. The mean loading dose was 86.07 mg, and the median continuous infusion dose was 57.97 mg/h. A population pharmacokinetic model fitting the plasma concentrations of lidocaine and its active metabolites was built to explore the factors affecting the concentrations of lidocaine and its active metabolites.Results: A two-compartment model with first-order elimination was used to determine the concentrations of lidocaine and its active metabolites. The different dosing simulations revealed that the selected appropriate loading dose did not exceed 1.5 mg/kg, and the continuous infusion dose of lidocaine should preferably not surpass 1.5 mg/kg/h in Chinese hepatectomy patients. The simulation results of long-term infusion of lidocaine during the postoperative stage after liver resection that showed there was a significant accumulation of MEGX after more than 24 hours of lidocaine infusion, and when the infusion rate reached 1 mg/kg/h, the MEGX concentration exceeded 5 μg/mL.Conclusion: This study proposes for the first time the integration of lidocaine concentration with active metabolites and simulation-based dosing recommendations. During the 24-hour medication period for Chinese hepatectomy patients, the recommended safe dosage includes a loading dose not exceeding 1.5 mg/kg and an infusion dose not exceeding 1.5 mg/kg/h. Monitoring of active metabolites, in addition to lidocaine is also necessary for continuous infusion of lidocaine.Trial Registration: The trial is registered at chictr.org.cn (ChiCTR2100042730).Keywords: hepatectomy, lidocaine, active metabolites, population pharmacokinetics, dose simulation